2023
DOI: 10.1371/journal.pone.0293411
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural network model by deep learning and teaching robot in keyboard musical instrument teaching

Jidong Liu,
Fang Fu

Abstract: Keyboard instruments play a significant role in the music teaching process, providing students with an enjoyable musical experience while enhancing their music literacy. This study aims to investigate the current state of keyboard instrument teaching in preschool education, identify existing challenges, and propose potential solutions using the literature review method. In response to identified shortcomings, this paper proposes integrating intelligent technology and subject teaching through the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On the other hand, most recent studies have found that short-term HFD can induce bone loss [ 44 , 45 ], while long-term HFD-exposed mice had reduced bone mass, which may be mainly due to the increase in adipocytes by affecting the bone marrow microenvironment [ 46 ]. Although healthy weight gain can benefit bone health by increasing the load-bearing capacity, these benefits may be lost in the case of HFD-induced weight gain [ 47 ]. A survey of a population’s bone mineral density and lifestyle habits showed that fatty diets were the most important risk factor for early bone loss in women, except for genetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, most recent studies have found that short-term HFD can induce bone loss [ 44 , 45 ], while long-term HFD-exposed mice had reduced bone mass, which may be mainly due to the increase in adipocytes by affecting the bone marrow microenvironment [ 46 ]. Although healthy weight gain can benefit bone health by increasing the load-bearing capacity, these benefits may be lost in the case of HFD-induced weight gain [ 47 ]. A survey of a population’s bone mineral density and lifestyle habits showed that fatty diets were the most important risk factor for early bone loss in women, except for genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is important to note that other factors should also be considered in the use of the neural network model, the accuracy and stability of the model should be further verified and adjusted [ 47 ]. Firstly, age is an important variable that is usually closely related to bone health.…”
Section: Discussionmentioning
confidence: 99%
“…CNNs is a class of DL models specifically designed to process data with a grid structure, it is mainly composed of convolutional layer, activation function, pooling layer and fully connected layer. Because of its automatic feature extraction, parameter sharing and spatial invariance, CNNs is widely used in various image processing tasks and in DL [ 47 , 48 ]. Other common used DL networks and reasoning models also include RNNs, Generative Adversarial Networks (GANs), Variational Autoencoders (VAEs) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our approach uses a deep convolutional recurrent neural network (CRNN) to extract and classify high-level spectro-temporal audio features. 3 Uncertainty sampling based on the model's predictive entropy identifies the most informative instances for labeling.…”
Section: Introductionmentioning
confidence: 99%